Literary Practices and Nationalism: Revisiting Mexican Nationalist 1932 Debate (Anclajes, 2024)
The nationalist controversy of 1932 is a key episode in the history of the professionalization of the writer in Mexico. Until now, studies on that year’s debates have emphasized the existence of two sides, separated by their own ideas about the content of the literature that the new post-revolutionary state should promote. By opening the scope and contextualizing the dispute as a result of the complex process of state formation, the cultural nationalism promoted, among others, by Ermilo Abreu Gómez and Héctor Pérez Martínez, can be understood as a product of the material conditions in which the written word is produced, circulated and received. This article rereads and analyzes the documents of the controversy, including letters, articles and journalistic reports, in order to determine how ideas about literature in Mexico depend on the limitations of the autonomy of the intellectual, which hinder thinking of writing as a profession.
Keywords: Nationalist Debate; Mexico 1932; Intellectuals; Newspapers and Magazines; Literature as a Profession